Why do banks fail? The role of bank-specific and macroeconomic variables - Korhonen, Anniina (My University, 2020)
This paper studies bank failures in EU-12 countries before and after the financial crisis of 2007-2008. Logit regression is used to examine how bank specific and macroeconomic factors affect a probability of a bank failure between 2006 and 2012. A behavior of bank specific factors four years before a bank failure is further studied in order to draw conclusions how the variables change over time. Lastly, a number of predicted bank failures before and after 2012 is calculated to see whether the number is decreased since the crisis. The results show that both bank specific and macroeconomic factors are important when forecasting bank failures. Especially size is a highly significant factor and contrast to the "too-big-to-fail", an increase in size increases a probability of a bank failure. Further examining of bank specific variables show that they behave differently over time and certain factors tend to change significantly several years before a failure whereas some change just before a failure. Lastly, even though the analysis shows that a number of predicted bank failures has decreased after the financial crisis, it is not clear whether it is a result of changes in bank regulation and supervision.
Keywords: banks (monetary institutions); banking crises; financial crises; failure; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance